2013
DOI: 10.1002/jgrb.50299
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake synchrony and clustering on Fucino faults (Central Italy) as revealed from in situ36Cl exposure dating

Abstract: [1] We recover the Holocene earthquake history of seven seismogenic normal faults in the Fucino system, central Italy. We collected 800 samples from the well-preserved limestone scarps of the faults and modeled their 36 Cl concentrations to derive their seismic exhumation history. We found that > 30 large earthquakes broke the faults in synchrony over the last 12 ka. The seven faults released strain at the same periods of time, 12-9 ka, 5-3 ka, and 1.5-1 ka. On all faults, the strain accumulation and release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
198
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(218 citation statements)
references
References 97 publications
(235 reference statements)
19
198
1
Order By: Relevance
“…In particular, it is not clear if the distribution of recurrence intervals is best described by a renewal model with a strong central tendency [Matthews et al, 2002], by the view that repeated large earthquakes can happen in rapid succession without requiring time for stress regeneration [Jackson and Kagan, 2006] or that strain is released by clustered events in a time span considerably shorter than their mean recurrence interval [Wallace, 1987]. A recent 36 Cl exposure dating study of the fault scarps of the Fucino fault system [Benedetti et al, 2013] suggests that over the last 12,000 kyr, >30 large earthquakes broke the faults in synchrony in 3-6 kyr spaced clusters of large events releasing most of the strain in <1-2 kyr long episodes. If these results are generalized, there emerges a general scenario where migrating pulses of activity are temporarily focused for a timescale of few thousand years, similarly to what is proposed for the Basin and Range province [Wallace, 1987].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it is not clear if the distribution of recurrence intervals is best described by a renewal model with a strong central tendency [Matthews et al, 2002], by the view that repeated large earthquakes can happen in rapid succession without requiring time for stress regeneration [Jackson and Kagan, 2006] or that strain is released by clustered events in a time span considerably shorter than their mean recurrence interval [Wallace, 1987]. A recent 36 Cl exposure dating study of the fault scarps of the Fucino fault system [Benedetti et al, 2013] suggests that over the last 12,000 kyr, >30 large earthquakes broke the faults in synchrony in 3-6 kyr spaced clusters of large events releasing most of the strain in <1-2 kyr long episodes. If these results are generalized, there emerges a general scenario where migrating pulses of activity are temporarily focused for a timescale of few thousand years, similarly to what is proposed for the Basin and Range province [Wallace, 1987].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to long-term temporal changes in slip rate that have been inferred (Goldfinger et al, 2013;Wallace, 1987;Weldon et al, 2004) or shown elsewhere (Benedetti et al, 2013;, the present study uses direct measurements of both age and offset to document a discrete, short pulse of accelerated slip along a major, long-lived strike-slip fault. Based on its duration and magnitude, we conclude that the mid-Holocene slip pulse resulted from either a spatiotemporal cluster of events or a single great earthquake.…”
Section: Secular Variation In Slip Along the Altyn Tagh Faultmentioning
confidence: 96%
“…Stress changes between interacting faults Stein, 1999;Stein et al, 1994) can synchronize slip behavior (Benedetti et al, 2013;Scholz, 2010). The North Altyn fault (NAF) is a candidate structure with which the ATF may interact (Figs.…”
Section: Alternative Mechanismsmentioning
confidence: 98%
“…Moreover, long-term observations of faults in various tectonic contexts have shown that slip rates vary in space and time (e.g. Bull et al, 2006;Nicol et al, 2006Nicol et al, , 2010 , 2009a, b;Gunderson et al, 2013;Benedetti et al, 2013;D'Amato et al, 2016), and numerical simulations (e.g. Robinson et al, 2009;Cowie et al, 2012;Visini and Pace, 2014) suggest that variability mainly occurs in response to interactions between adjacent faults.…”
Section: Slip Ratesmentioning
confidence: 99%